Immunoregulatory mechanisms in the lungs of mice and humans - Coleman, Michelle (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
The lungs are constantly exposed to inhaled antigen during respiration. The resident immune cells must be hyporesponsive to innocuous inhaled antigen, yet capable of responding appropriately to respiratory pathogens, with minimal immunopathology to the fragile lung tissue. Regulatory T (Treg) cells are crucial for the maintenance of immune tolerance in the lungs. Alveolar macrophages (AM) also contribute to the local immunosuppressive environment of the lungs.
Keywords: Biochemistry and Immunology, Ph.D.; Ph.D. Trinity College Dublin.